New records of water mites (Acari: Hydrachnidia) from the Khuzestan Province (South Iran) with description of three new species - Pešić, Vladimir; Asadi, Mahdieh; Etemadi, Isa; Smit, Harry (Zootaxa, 2019)
New records of water mites (Acari: Hydrachnidia) from the Khuzestan Province of Iran are presented. Three species, i.e. Torrenticola khuzestanica, T. neoungeri (Torrenticolidae), and Atractides khuzestanicus (Hygrobatidae) are described as new to science.